2000
DOI: 10.1063/1.127076
|View full text |Cite
|
Sign up to set email alerts
|

Self-induced light polarization rotation in azobenzene-containing polymers

Abstract: We report here a light-induced phenomenon—a self-induced rotation of the azimuth of elliptically polarized light passing through photobirefringent azopolymers. The experiments are carried out with films of amorphous and liquid-crystalline polymers. It has been shown that the induced rotation angle depends on the ellipticity of the input light. A theoretical analysis of the phenomenon has been done and it has been shown that light induces chiral structure in the polymer films.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
85
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(87 citation statements)
references
References 6 publications
2
85
0
Order By: Relevance
“…As the ellipticity of the beam increased further, the induced CD became smaller, and when the beam profile approached to circularly polarization state, the CD signal became negligible again. Even though dependence of ellipticity on optical rotation was reported [5], this kind of strong dependence of ellipticity on induced circular dichroism has never been reported before. We are currently investigating the detailed mechanism of this process and the nature of the induced CD.…”
Section: Resultsmentioning
confidence: 87%
“…As the ellipticity of the beam increased further, the induced CD became smaller, and when the beam profile approached to circularly polarization state, the CD signal became negligible again. Even though dependence of ellipticity on optical rotation was reported [5], this kind of strong dependence of ellipticity on induced circular dichroism has never been reported before. We are currently investigating the detailed mechanism of this process and the nature of the induced CD.…”
Section: Resultsmentioning
confidence: 87%
“…Photoinduced circular anisotropy was found to depend on the nature of the excitation light (such as its ellipticity, beam intensity, wavelength and irradiation time) [188][189][190][191]. Although the chemical structure of the polymer main-chain employed by each study was different (ester, epoxy, and methacrylate, for example) the proposed mechanism for the generation of the photoinduced chirality was identical.…”
Section: Supramolecular Chiralitymentioning
confidence: 84%
“…Nikolova and coworkers reported that the rotation angle depends on the function Δn·e/(1 − e 2 ) [188]. (Here, the terms "Δn" and "e" represent photoinduced birefringence and ellipticity, respectively.)…”
Section: Supramolecular Chiralitymentioning
confidence: 99%
“…This reorientation continues throughout the film depth. Overall, a chiral ordering of the chromophore domains is established (Nikolova et al, 2000). Remarkably, one can switch between a right-and left-handed supramolecular helix at will, by changing the incident light handedness.…”
Section: Domain Motionmentioning
confidence: 96%